The Effect of Spiritual Leadership and Nurse Performance Through Quality of Work Life and Job Satisfaction (Study in RSUD dr. Doris Sylvanus Palangka Raya) - Yacinda Chresstela Prasidya Norianggono; Danes Jaya Negara; Roby Sambung (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
Job satisfaction and quality of work life as mediating variable in this research. This study aims to examine and assess the connection between spiritual leadership and the performance of nurses. The 152 nurses that participated in this study were millennial nurses with the status of Civil Servant ranging in age from 27 to 42 in dr. Doris Sylvanus Hospital Palangka Raya, Smart PLS 4.0 was used for data analysis. The research results indicate that spiritual leadership does not significantly impact nurse performance, Meanwhile, the quality of work life affects the performance of nurses. In addition, spiritual leadership has a significant influence on the job satisfaction and quality of work life, there was a significant influence between job satisfaction on nurse performance and quality of working life does not have a significant influence on nurse performance. The mediating role of quality of work life on the relationship between spiritual leadership and nurse performance had no significant effect. However, nurse performance is strongly influenced by spiritual leadership mediated by job satisfaction.